Polymer Interphase Self‐Reinforcement and Strengthening Mechanisms in Low‐Loaded Nanocomposite Fibers. Issue 12 (29th April 2015) - Song, Kenan; Zhang, Yiying; Minus, Marilyn L.
<x xml:space="preserve">Abstract</x> The effect of filler concentration on understanding structure–property relationships in polymer composites with low nanocarbon (nC) loadings (<1 wt%) is investigated. The presence of the carbon nanochips (CNC) filler induces the formation of highly ordered self‐reinforcing interphase regions within the composite fibers. The influence of these regions on the structure and properties of the fibers is analyzed by both theoretical and experimental methods. Analysis of the filled polyvinyl alcohol (PVA) fibers demonstrates that the presence of the nC influences the organization and formation of crystalline and amorphous polymer lamellae stacking in the fibers, leading to variations in grain structure for the composites. These structural developments contribute specifically to the property increases (i.e., elastic modulus increased by 222% and tensile strength increased by 186%) for the PVA/CNC composites in comparison to control PVA fibers.